Determinant Factors of Voluntary Adoption of Mobile Money In Indonesia - Ricardo Indra; Husnita Husnita (Syntax Literate, 2022)
Humans are faced with technological developments that can have life-changing social impacts. The presence of technology in society is now inevitable, such as mobile money for all activities in daily life. A quantitative approach is used to find innovation characteristics as a determinant of the technology adoption process through the Innovations Diffusion Theory (IDT) method. This study describes the voluntary adoption of mobile money, in contrast to adoption due to regulation. The adoption process in IDT states that individual decisions are determined by the main predictor, namely the characteristics of the innovation. This quantitative survey takes LinkAja respondents as mobile money users. Data processing using SEM with LISREL 8.70. Relative Advantage, Compatibility, Trialability, and Observability positively influence the adoption of mobile money. Trialability does not have a positive influence on the adoption process. The importance of the five innovative characteristics in influencing the adoption process and implications for researchers and practitioners. IDT can be used to predict how the process of adoption of mobile money effectively. It needs socialization by providing basic knowledge that can build understanding.